How the Brazilian Workers are Dealing with Return-To-Work Post-Pandemic: An Unchartered Territory - Schmitz, Thiago; Dias, Murillo (European Journal of Applied Sciences, 2024)
COVID-19 has caused instability and uncertainty in various aspects of life, including labor relations. This article explores the return-to-work (RTW) scenario in the Brazilian IT sector, the top ten largest global IT market. The research focuses on the employee’s perspective, addressing a gap in understanding productivity effects. Through Focus Groups and In-depth Interviews, the study found a trend of adhesion to three work modalities: face-to-face, hybrid, and teleworking, contrary to other industries. The findings highlight the need for further analysis and discussion on RTW post-pandemic.